Ruptures and Resolutions of the Therapeutic Alliance in a Case of Insecure Attachment - González Vergara, Tamara Mailen; Pizarro Concha, Álvaro Wladimir; Dufey, Michele (Revista de Psicología, 2022)
This study aims to understand the development of alliance ruptures and resolutions in an insecure-attached client. A single-case study was implemented in an individual brief focusing-oriented psychotherapy. Rupture Resolution Rating System was applied (3RS; Eubanks, Muran, & Safran, 2015) to therapy sessions transcripts, and illustrative vignettes were extracted to determine therapy issues related to ruptures and resolutions. The results show 16 ruptures markers with a higher prevalence of “complains/concerns about activities of therapy” marker, which was thematically related to difficulties of the client to perform emotional exploration activities offered by the therapist. Likewise, nine resolutions attempts were observed, being the most used strategy “the therapist illustrates a task or provides a rationale for treatment”. Attachment related difficulties on the emotional regulation of the client at ruptures occurrence are discussed, as well as effective resolution attempts by the therapist, which may serve as a guidance for therapeutic work with insecure-attached clients.